Pengaruh Sosialisasi dan Komitmen Profesi Pegawai Pajak Terhadap Niat Whistleblowing - Sekar Akrom Faradiza; Kartika Candra Suci (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
Whistleblowing system is created to overseeing the violation of the code of ethics that occured within the Directorate General of Taxation (DGT) by utilizing all its employees. These system is based on three principles that are prevention, early detection and effective handling. The aims of this study are to examine the effect of socialization on whistleblowing and professional commitment of tax office’s employees to whistleblowing intention. The population in this study is employees in DGT on Yogyakarta and Central Java. This research used survey to collect data from 92 employees. Multiple regression linear is used to data analyzed. The result showed significant effect of socialization to whistleblowing intention. Unexpected finding is professional commitment did not effecting whistleblowing intention.